2012
DOI: 10.1116/1.4736552
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron yield on cryogenic surfaces as a function of physisorbed gases

Abstract: In LHC the electron cloud induced by photoelectrons, gas ionization and secondary electrons emitted from the beam pipe walls could be a limitation of the performance. The electron cloud induce heat load on the cryogenic system, cause pressure rise, emittance growth and beam instabilities, which in the end will limit the beam"s lifetime. Beam-induced multipacting, which can arise through oscillatory motion of photoelectrons and low-energy secondary electrons bouncing back and forth between opposite walls of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
8
27
0
Order By: Relevance
“…After irradiation of the samples with doses of 6.1 × 10 −6 C mm −2 and up to 1.8 × 10 −5 C mm −2 (corresponding to 5 and 10 min of constant irradiation, respectively, similar to what done on the CH-patterned samples), a progressive reduction of the SEY values is observed which remains stable upon further measurements. This conditioning process might be ascribed to desorption of surface adsorbates [14]. The behavior of the sample treated in air is entirely different but similar to that already reported for CHpatterned samples.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…After irradiation of the samples with doses of 6.1 × 10 −6 C mm −2 and up to 1.8 × 10 −5 C mm −2 (corresponding to 5 and 10 min of constant irradiation, respectively, similar to what done on the CH-patterned samples), a progressive reduction of the SEY values is observed which remains stable upon further measurements. This conditioning process might be ascribed to desorption of surface adsorbates [14]. The behavior of the sample treated in air is entirely different but similar to that already reported for CHpatterned samples.…”
Section: Resultssupporting
confidence: 76%
“…As discussed in Ref. [14], this dose is well below the level of damage of the adsorbates and cannot produce any substantial surface modification. Stability of the SEY under electron bombardment ("conditioning") is investigated by continuous irradiation at an electron energy of 250 eV, the beam current being approximately doubled and the beam size increased from 7 to 11 mm 2 , in order to cover an area larger than the measurement spot.…”
Section: B Sample Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Obtained results coupled with those of literature 10,[13][14][15][16] indicate that baked and scrubbed copper coating can achieve a SEY max of 1. For completeness, it should be pointed out that recently, it has been shown that well-scrubbed stainless steel, by electrons and positrons, 19 can have its SEY max reduced to 1.3.…”
Section: Coatings Rf Resistivity and Seysupporting
confidence: 83%
“…27, where we report SEY as measured on a copper surface held at 4.7 K as a function of increasing CO coverage. 140 Already a single CO ML physisorbed on the Cu cold surface significantly modifies its SEY and additional CO deposition results in a completely different SEY value of about 1.2. This result is not only very important to confirm the extreme surface sensitivity of SEY but suggests that, when discussing SEY of cold surfaces (like for the LHC dipoles) great care must be taken in considering any eventual surface modification induced by gas physisorption.…”
Section: Secondary Electron Yield Of Technical Surfacesmentioning
confidence: 99%